Cross-country price and inflation dispersion: Retail network or national border? - Teresa Messner; Fabio Rumler; Georg Strasser (European Central Bank (ECB), 2023)
(Why) do prices and inflation rates differ within the euro area? We study the relevance of a national border for grocery prices in the otherwise homogenous and highly integrated border region of Austria and Germany. Using transaction data on prices and quantities from a large household panel, we compare the prices of identical products within a narrow band along the border. We find large assortment and price differences between these two regions. Even within multinational retail chains the prices of identical products on the two sides of the border differ on average by about 21%. These price differences are not very persistent indicating little arbitrage gain from undifferentiated cross-border shopping. Ensuing product-level inflation rates differ for only half of the chains. The results highlight the importance of the history-dependent evolution of distribution networks and of the structure of the sales organization as a driver of price and inflation heterogeneity.
Keywords: D12; E31; D43; F15; F4; 330; Price discrimination; goods market integration; border effect; cross-border arbitrage; market power